The Burden of Respiratory Syncytial Virus Disease in Children and Adults Hospitalized in a Large Tertiary Hospital in the United Kingdom: A Retrospective Study. Issue 12 (22nd September 2022) - Knapper, Francesca; Ellis, Josephine; Bernatoniene, Jolanta; Williams, Philip
Abstract : Respiratory syncytial virus (RSV) is an RNA virus spread via droplets. Children are predominately affected, with a significant burden in the under 1s. The burden of disease across both children and adults and management is rarely reported. We completed a retrospective study looking at the characteristics of all patients admitted with a positive RSV PCR throat swab were reviewed from a large tertiary hospital in the United Kingdom over the 2019/2020 season. Four hundred six paediatric patients and 81 adult patients were included. Ninety-four percent (76/81) of adult patients had comorbidities compared with 20% (81/406) of children. In adults Chest radiograph was normal in 46% (37/81). Thirty-six percent (29/81) showed consolidation. Viral coinfection was common among children 158 (39%). Forty (10%) of children were admitted to pediatric intensive care and 7 (9%) of adults were admitted to intensive care unit. No children and 6 (7%) of adults admitted with RSV died. RSV is associated with a significant morbidity. Mortality in adults admitted to Intensive Care Unit was high. Coinfection with other viruses is common in children. The use of antibiotics was higher than expected, although C-reactive protein and Chest radiograph suggested secondary bacterial infection is more common in adults.